The infrared and Raman spectra of potassium azidopentacyanocobaltate(III) dihydrate: K3[Co(CN)5N3]·2H2O - Amalvy, Javier Ignacio (1983)
Infrared spectra of potassium azidopentacyanocobaltate(III) dihydrate (PACDH) were obtained from the polycrystalline substance, both normal and deuterated, and from the monocrystal using in this case a polarization analyzer. Raman spectra of the normal powder were also obtained. The observed bands were assigned either to the internal vibrational modes of the azidopentacyanocobaltate(III) ion (AC) or to the internal and librational modes of the hydration water.